2022
DOI: 10.58845/jstt.utt.2022.en.2.2.22-31
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence approach to predict the dynamic modulus of asphalt concrete mixtures

Thanh-Hai Le,
Hoang-Long Nguyen,
Cao-Thang Pham

Abstract: This paper develops an Artificial Neural Network (ANN) model based on 96 experimental data to forecast the dynamic modulus of asphalt concrete mixtures. The accuracy of the models was assessed using numerous performance indexes such as the Root Mean Square Error (RMSE), Mean Absolute Error (MAE), Mean Absolute Percentage Error (MAPE), and coefficient of determination (R2). In addition, this study applied the repeated K-Fold cross-validation technique with 10 folds on the training data set to make the simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that machine learning evaluation performance can be improved when an optimization approach is applied to fine-tune model hyperparameters instead of performing manual trial-and-error calibration [5][6][7]. This is evident in the results reported in [8][9][10][11][12] in the prediction of E*.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that machine learning evaluation performance can be improved when an optimization approach is applied to fine-tune model hyperparameters instead of performing manual trial-and-error calibration [5][6][7]. This is evident in the results reported in [8][9][10][11][12] in the prediction of E*.…”
Section: Introductionmentioning
confidence: 99%